Trade openness and non-income poverty in Southern African Development Community (SADC) countries: A panel Autoregressive Distributive Lag (ARDL) analysis - Dorcas Gonese; Asrat Tsegaye; Sibanesizwe Alwyn Khumalo; Kapingura Forget Mingiri (Cogent Economics & Finance, 2023)
The paper examines the effect of trade openness on poverty using the panel Autoregressive Distributive Lag (ARDL) estimation technique from 1980 to 2019 in Southern African Development Community (SADC) countries. The paper focuses on non-income poverty; in this paper, non-income poverty is measured by the human development index since this measure looks at poverty beyond just income. The paper assesses the direct and indirect effects by including the mediating variables in the non-income poverty trade openness model. The study results assist SADC governments and policymakers in addressing poverty reduction policies amid the trade openness era and identifying appropriate complementary policies for reducing poverty in SADC countries. The study's findings indicate that trade openness reduces non-income poverty (NPOV) in SADC countries in the long run. Again, the empirical results suggest that trade openness reduces NPOV when economic growth and human capital development are high. Yet, trade openness worsens NPOV when income inequality increases. Surprisingly an inconsistent result indicates that a mediating variable of trade openness and financial development has a negative effect on NPOV in SADC countries. This calls for SADC governments and policymaking institutions to revamp the trade opening reform by making economic growth sustainable and inclusive, improving the education system's quality, maintaining income distribution, and making pro-poor financial systems across the region.
Keywords: 330; Poverty; Trade Openness; SADC; Pooled Mean Group